Genetic Diversity of Canine Circovirus Detected in Wild Carnivores in Serbia - Damir Benković; Jakov Nišavić; Nenad Milić; Dejan Krnjaić; Isidora Prošić; Vladimir Gajdov; Nataša Stević; Ratko Sukara; Martina Balać; Andrea Radalj (Veterinary Sciences)
Canine circovirus (CanineCV) is an emerging virus of interest in both domestic and wild carnivores that is scarcely reported in southeastern Europe. This study examined the presence, genetic diversity, and evolutionary characteristics of CanineCV in red foxes (Vulpes vulpes) and golden jackals (Canis aureus) from northwestern Serbia, a region marked by expanding mesopredator populations overlapping with human habitats. Out of 98 sampled animals, circoviral DNA was detected in 31.6%. Jackals were mostly positive for CanineCV genotype 4, while genotype 5, associated with wild carnivores, was dominant in foxes. Mixed genotype 4/genotype 5 infections were only found in jackals. Phylogenetic and haplotype analyses indicated that most jackal-derived CanineCV strains clustered along sequences from Europe, Africa, and the Americas, while genotype 5 sequences grouped separately from other genotype representatives. A recombinant strain was identified as a divergent lineage, and several sequences showed evidence of recombination between Rep and Cap genes. Despite Cap protein amino acid differences, purifying selection dominated, suggesting functional constraints on viral evolution. The results indicate that jackals may act as recombination hotspots and bridging hosts between viral lineages. This study provides insight into the molecular epidemiology of CanineCV in the Balkans, highlighting the importance of ongoing surveillance.